Gender overeducation gap in the digital age: Can spatial flexibility through working from home close the gap? - Santiago Vela, Ana [Verfasser]; Mergener, Alexandra [Verfasser] (My University, 2022)
“This study analyses the gender overeducation gap, meaning differences between partnered men and women in the degree of holding a job with lower requirements compared to one’s own education, and how working from home (WfH) affects overeducation. Contextualising education–job mismatches in the digital age, we update an old topic of labour market research considering new options of spatial flexibility via WfH. Using a unique German dataset of the core employed population in 2018 (i.e., individuals that are at least 15 years old and report paid work for at least 10 h per week), our results show a gender overeducation gap, with women at a higher risk of overeducation than men. By applying a latent variable approach with simultaneous regressions to account for potential selection into jobs allowing WfH, we find that the WfH option carries a lower overeducation risk. Moreover, the findings suggest a gender-specific benefit of WfH: women show higher overeducation risks among employees without the WfH option, but the gender overeducation gap is closed among those with the WfH option.“ (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; G 2.3.3 Arbeitsformen, Techniken; G 2.4.5 Gender Mainstreaming; 370; 300; Arbeitsmarktforschung; Überqualifikation; Telearbeit; geschlechtsspezifische Faktoren